Appendiceal band syndrome as a cause of mechanical intestinal obstruction: A case report - Mudassar Fiaz Gondal; Hasnain Aslam; Jawad Jahnagir Abbassi; Usama Iftikhar; Shahzaib Maqbool; Ka Yiu Lee (Journal of Pediatric Surgery Case Reports, 2022)
Introduction and importance: Acute appendicitis is a common surgical emergency we encounter on surgical floor. Adynamic obstruction due to appendicitis and its related complications are seen very often; however, the mechanical obstruction is a rare happening associated with acute appendicitis. Case presentation: We reported a case of 7 years old boy, who presented with generalized abdominal pain more marked in right iliac fossa and abdominal distension as well. On clinical examination tenderness in RIF and guarding in lower abdomen was present. Complete blood picture was showing the leucocytosis and neutrophilia and rest of the laboratory findings were reference ranges. After making the patient clinically stable the retrograde appendectomy was performed. At operation, the vermiform appendix was found encircling a loop of terminal ileum like a band. The tip of appendix was gangrenous. The postoperative recovery was uneventful. Clinical discussion: This case was a rare happening of appendiceal band syndrome which is a rare diagnosis because its been not considered to have mechanical intestinal obstruction following a appendicular pathology. And having appendiceal band syndrome or tie it self is rare happening, however; having association with mechanical intestinal obstruction make this case even more interesting that need emergency appendectomy to relieve the symptoms and prevent complications. Conclusion: Appendiceal band syndrome is a rare happening that may cause acute intestinal obstruction and gut may become gangrenous due to break in blood supply and should be diagnosed at earliest and treated with open appendectomy.